Physics and Philosophy in Whitehead - Athearn, Daniel (Process studies, 2016)
An essay first published in 1917 presents key insights and ideas that shaped Whitehead’s physics and metaphysics. It also displays his apparently lifelong view that science cut off from philosophy (which for him meant, or at some point led to, metaphysics) will fall short in its vital mission of explaining facts and phenomena—a view dissenting sharply from reigning doctrines of the modern era. His largely implicit criticism of the modern assumption that science as such can do without philosophy merits clarification and evaluation.